Case Report: Repeated Low-Dose Rituximab Treatment Is Effective in Relapsing Neuro Behçet's Disease - Zhao, Chao; Li, Chuan; Duan, Feng-ju; Yan, Qi; Zhang, Zhuo; Du, Ying; Zhang, Wei (Frontiers in Neurology, 2021)
Neuro Behçet’s disease (NBD) is a rare but most aggressive manifestation of Behçet’s disease (BD) with a poor prognosis, and some patients even present a relapsing and treatment-resistant progressive course. To some relapsing NBD cases, traditional corticosteroids and immunosuppressive drugs show limited efficacy, while benefits of biological agents, such as anti-B-lymphocyte CD20 biological agent rituximab (RTX), gradually represent potential therapeutic advantages with clinical rapid remission and long-time maintenance. However, up to now, the optimal dosage of RTX in NBD is still elucidated. Here, we report 2 patients with relapsing NBD, despite continuous high dose steroids and sufficient azathioprine treatment, still presenting severe and relapsing meningoencephalitis or brainstem involvement. Repeated low-dose RTX (100mg×3 / 1 week apart, 100mg repeated every 6 months) is then tried with rapid recovery and sustained remission. The approach in our cases may expend therapeutic options and provide helpful references for relapsing NBD treatment.